VD_FINDINFO HC / 2012 / 4 vom 13. Dezember 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, REVENU HYPOTHÉTIQUE, OBLIGATION D'ENTRETIEN, CONJOINT | 163 al. 1 CC, 176 al. 1 ch. 1 CC, 143 al. 1 CPC (CH), 272 CPC (CH), 296 CPC (CH)